2012
DOI: 10.1037/a0029217
|View full text |Cite
|
Sign up to set email alerts
|

The association between neurocognitive functioning and smoking in adolescence: The TRAILS study.

Abstract: Objective: This study examines the association between neurocognitive functioning and tobacco smoking in adolescence. Method: Data from three measurements of the longitudinal Tracking Adolescents' Individual Lives Survey (TRAILS), a large regional population-based cohort study of Dutch adolescents, were used. The first measurement took place in 2001–2002 (T1) when participants were age 11, with two follow-up measurements (2003–2004 and 2005–2007; T2 and T3, respectively). A total of 1,797 adolescents participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
(57 reference statements)
2
13
0
2
Order By: Relevance
“…Another longitudinal study based on a large sample of Dutch adolescents found no significant effects of working memory on the likelihood of initiating smoking or becoming daily smokers a few years later. Although inhibition was not predictive of future daily smoking either, adolescents with low inhibition at ages 10–11 years were more likely to endorse that they have ever smoked at ages 15–17 years, compared to those with high inhibition (Harakeh et al, 2012). However, predicting complete abstinence throughout adolescence may not be as meaningful as evidence of early onset or patterns of substance use in predicting future abuse and addiction (e.g., Stone, Becker, Huber, & Catalano, 2012).…”
Section: Behavioral Studies Of Ef Related To Substance Usementioning
confidence: 71%
See 1 more Smart Citation
“…Another longitudinal study based on a large sample of Dutch adolescents found no significant effects of working memory on the likelihood of initiating smoking or becoming daily smokers a few years later. Although inhibition was not predictive of future daily smoking either, adolescents with low inhibition at ages 10–11 years were more likely to endorse that they have ever smoked at ages 15–17 years, compared to those with high inhibition (Harakeh et al, 2012). However, predicting complete abstinence throughout adolescence may not be as meaningful as evidence of early onset or patterns of substance use in predicting future abuse and addiction (e.g., Stone, Becker, Huber, & Catalano, 2012).…”
Section: Behavioral Studies Of Ef Related To Substance Usementioning
confidence: 71%
“…1999 Composite: Stroop;Porteus maze task;Vigilance task; Motorrestraint task;Forbidden toy task;Block design task 275 (106 high-risk youth; 169low-risk youth) 10–12(baseline) 100% male β = .28* to −2.25* a Giancola & Parker 2001 Composite: Porteusmaze task; Motorrestraint task;Vigilance task;Forbidden toy task;Block design task 187 (69 withfamily history ofsubstance usedisorder, SUD;21 with familyhistory other thanSUD; 97controls) 10–12(baseline) 100% male r = −.02 Giancola et al. 2001 Composite: Porteusmaze task; Motorrestraint task; Strooptask; Vigilance task;Block design task;Picture arrangementtask; Object assemblytask 282 (188 withsubstance usedisorder; 94controls) 14–18 100%female b * = −.16*/.08for low/highantisocial behaviorgroup Groenman et al 2015 Stop task; Shiftingattentional set task;Visuospacialsequencing; Digit spanbackward task 669 (294 ADHDprobands; 161unaffectedsiblings; 214controls) 11–12(baseline) 78%, 41%,39% male,respectively All p values > .05 Harakeh et al. 2012 Memory search taskand Shifting set task 1797 communityyouth 11(baseline) 49% male OR = 1.21 and 2.24* Jonker et al.…”
Section: Tablementioning
confidence: 99%
“…Smoking was assessed with the question: ‘How many cigarettes did you smoke in the past 4 weeks?’ Adolescents who had not smoked in the past 4 weeks were categorized as non‐smokers. Adolescents who had smoked less than one cigarette a day in the past 4 weeks were categorized as non‐daily smokers and those who had smoked one or more cigarettes per day as daily smokers (Harakeh et al ). Cannabis use was assessed with the question: ‘How many times have you used weed (marijuana) or hash in the past 4 weeks?’ Adolescents who had not used cannabis in the past 4 weeks were categorized as non‐users.…”
Section: Methodsmentioning
confidence: 99%
“…Adolescents who had not smoked in the past 4 weeks were categorized as non-smokers. Adolescents who had smoked less than one cigarette a day in the past 4 weeks were categorized as non-daily smokers and those who had smoked one or more cigarettes per day as daily smokers (Harakeh et al 2012). Cannabis use was assessed with the question: 'How many times have you used weed (marijuana) or hash in the past 4 weeks?'…”
Section: Substance Usementioning
confidence: 99%
“…Fernie et al (2013) showed that poor performance in the Stop-Signal task predicted later alcohol involvement, while alcohol involvement did not predict later performance in this task. Mixed results have also been produced with tobacco outcomes, with most studies failing to identify a significant effect (Galvan et al, 2011; Groenman et al, 2015; Harakeh et al, 2012; Smith et al, 2014). Further, most studies with adolescent samples included in the meta-analysis by Smith et al (2014) showed small and nonsignificant associations between prepotent response inhibition and drug use.…”
Section: Review Of Impulsive Behavior and Drug Use In Adolescence mentioning
confidence: 99%